78Gy with Fiducial Marker Image‐Guided Radiotherapy in Prostate Cancer: Single Center Analysis of 301 Patients. Issue 5 (10th November 2016) - Choong, Ee Siang; Hruby, George; Yang, Jean; Kwong, Carol; Patanjali, Nitya
Abstract: Aim: In prostate cancer, fiducial marker image‐guided radiotherapy (FMIGRT) allows correction of setup errors and interfraction physiological motion resulting in improved accuracy of target and sparing of at risk organs. We aim to report outcomes and toxicities observed in patients treated with dose escalation to 78Gy with FMIGRT in our center. Methods and Materials: Retrospective review of consecutive patients with histologically confirmed T1‐4N0M0 localized prostate cancer treated with dose escalation to 78Gy with FMIGRT in our center. All patients had 3‐D conformal radiotherapy. Duration of androgen deprivation therapy use was tailored to risk group. Toxicity was scored according to CTCAE.v04. Kaplan–Meier analysis was performed for freedom from biochemical failure (FFBF), prostate cancer‐specific survival and overall survival. Results: Median follow‐up was 48.6 months. Median duration of androgen deprivation therapy was 6 and 23 months in the intermediate‐ and high‐risk group, respectively. FFBF at 5 years was 88.8%. FFBFs when stratified to risk groups were 100% for low risk, 88.9% for low‐intermediate risk, 89.9% for high‐intermediate risk and 85.4% for high risk, respectively. Acute severe toxicity (grade≥3) rate for both genitourinary (GU) and gastrointestinal (GI) was 1%. Late moderate‐to‐severe toxicity (grade≥2) rates for GU and GI were 15% and 17%, respectively, with severe (grade≥3) toxicity rate for GU and GI at 2% and 3%, respectively. Conclusion: Dose escalation to 78Gy with FMIGRT in our series achieved good FFBF at 5 years with low acute and late toxicity rates. These results provide a good comparator cohort to our current use of image‐guided intensity modulated radiotherapy.